A Rare Differential Diagnosis for Acute Abdominal Pain- Torsion Lipoma of Greater Omentum - Munikumar Amburu; Mohammed Zakariya Abdul Rezak; Loganathan Mannu Achari; Natarajan Ramalingam; KarunaNITHI Ramaiah (International Journal of Anatomy Radiology and Surgery, 2021)
Lipoma is a benign neoplasm arising from yellow fat. Often it can be hyperplasia or combination of neoplasm and hyperplasia. It is composed of mature adipocytes and uniform nuclei that are identical to those seen in normal adult fat. It is called as universal tumour/ubiquitous tumour as it can occur anywhere in the body outside of brain. It can be localised (encapsulated) or diffuse (nonencapsulated). It can occur in sites like subcutaneous, subfascial, intramuscular, intermuscular in anterior abdominal wall, paraosteal, submucosal, subserosal sites. Here, a case of torsion of the lipoma in the greater omentum is reported presenting as acute abdomen. This eight-year-old girl presented with symptoms of right iliac fossa pain, signs of localised peritonitis and right psoas irritation. Appendicular mass/abscess was considered on clinical examination. The radiological evaluation ruled out appendicular pathology and an ovarian pathology possibly a torted ovary was suspected. During surgical exploration, a tumour of greater omentum was identified and resected. This rarity of the differential diagnosis for a right Iliac fossa mass is highlighted herewith.